La plaine de la Crau (ouest de la Provence), un territoire aux enjeux socio-économiques et écologiques en mutation - Gérard Beltrando (Cybergeo)
The Crau Plain, a dried paleo delta of the Durance river, is a steppe grazed by sheep since over 4000 years, which has allowed the formation of a unique ecosystem. Since the construction of irrigation channels in the late sixteenth century, a part of the plain was transformed into hay meadows which produce highly nutritious fodder. It allowed the establishment of a "Pastoral system – Foin de Crau" and the creation of a connection between this irrigated part and the steppe; secondly, it enabled the formation of abundant groundwater which is necessary to 270 000 people and local economic activities. Since the early twentieth century, the plain has seen the intensification of artificial surfaces to the detriment of the steppe but also of irrigated areas at the benefit of urbanization and economic activities (military, transportation, logistics platform, garbage, market gardening, arboriculture...). The main activities and traditional functions of the plain, which are related to each other, change quickly in a context of strong pressure on the territory: (1) the surface used for the regular flooding of the hay meadows has shrinked, even though the flood supplies a large groundwater in which 80 million cubic meters of water are withdrawn each year; (2) similarly, the pastoralism reserved area for seasonal sheep grazing that allows to maintain a unique biodiversity in the arid steppe has dwindled. These rapid changes in land use now question both the sustainability of the aquifer which provides many ecosystem advantages to people and the upkeep, and even the reconstruction, of a unique biophysical environment of major ecological interest.